Comorbidity in Dementia: Update of an Ongoing Autopsy Study - Shino Magaki; William H. Yong; Négar Khanlou; Spencer Tung; Harry V. Vinters (2014)
Objectives To examine systemic and central nervous system ( CNS ) comorbidities of individuals with dementia evaluated during general autopsy. Design Retrospective cohort study. Setting A large tertiary academic medical center in Los Angeles, California. Participants Individuals with clinically and neuropathologically diagnosed dementia who received complete autopsies (n = 86) and individuals with dementia who received partial (brain only) autopsies (n = 132). Measurements Information on cause of death and systemic and CNS comorbidities was obtained from autopsy reports and clinical information as available from the medical records. Findings were tabulated with respect to type of dementia, semiquantitative assessment of the severity of cerebral amyloid angiopathy, semiquantitative assessment of the severity of cerebrovascular disease, and evidence of ischemic damage in the brain. Results Of 218 subjects with dementia, 175 (80.3%) had Alzheimer's disease alone or in combination with other lesions that might contribute to cognitive impairment, such as cerebrovascular disease and diffuse Lewy body disease ( DLBD ), 14 (6.4%) had frontotemporal dementia, and seven (3.2%) had isolated DLBD . The most common cause of death in participants with dementia was pneumonia (n = 57, 66.3%), followed by cardiovascular disease (n = 14, 16.3%). Eighteen subjects (20.9%) had lung disease, and 16 (18.6%) had evidence of an old or recent myocardial infarction. Clinically undiagnosed neoplasms included colonic adenocarcinoma, metastatic pulmonary neuroendocrine carcinoma, meningioma, and Schwannoma. Conclusion Significant comorbidities were discovered at autopsy in individuals with dementia. Understanding the causes of death and associated comorbidities in individuals with various subtypes of dementia is important in the assessment of end‐of‐life care in these individuals.